Effectiveness of One-Stop Screening for Colorectal, Breast, and Prostate Cancers: A Population-Based Feasibility Study - Sung, Joseph J. Y.; Luk, Arthur K. C.; Ng, Simon S. M.; Ng, Anthony C. F.; Chiu, Peter K. F.; Chan, Emily Y. Y.; Cheung, Polly S. Y.; Chu, Winnie C. W.; Wong, Sunny H.; Lam, Thomas Y. T.; Wong, Samuel Y. S. (Frontiers in Oncology, 2021)
Colorectal cancer (CRC), prostate cancer (PC) and breast cancer (BC) are among the most common cancers worldwide with well-established screening strategies. We aim to investigate the effectiveness and compliance of a one-stop screening service for CRC, PC and BC. Asymptomatic subjects aged 50–75 years were invited. Eligible subjects were offered fecal immunochemical test (FIT) for CRC screening. Serum prostate specific antigen (PSA) and Prostate Health Index (PHI) were offered for male PC screening and mammogram (MMG) for female BC screening as a one-stop service. Colonoscopy was offered to FIT+ subjects, prostate biopsy to PSA/PHI+ (PSA>10/PHI≥35) males and breast biopsy to MMG+ (Breast Imaging-Reporting and Data System, BI-RADS≥4) females. From August 2018 to April 2020, 3165 subjects were recruited. All participants (1372 men and 1793 women) were willing to accept FIT for CRC screening, and PSA/PHI test or MMG as second cancer screening. 102 subjects diagnosed advanced neoplasms after colonoscopy. Thirty-three males diagnosed PC after prostate biopsy and 15 females diagnosed BC after breast biopsy. No major complication reported in first tier screening tests. Subjects who were willing to undergo CRC screening were highly likely to accept other cancer screening when offered in a one-stop program. In conclusion, the effectiveness and compliance of a one-stop service for CRC, PC, and BC screening among asymptomatic subjects were high. Future studies should be conducted to test various ways of integrating cancer screening programs. Clinical Trial Registration ClinicalTrials.gov, identifier NCT04034953.